2015
DOI: 10.1139/cjpp-2015-0103
|View full text |Cite
|
Sign up to set email alerts
|

Acute inhibition of monoamine oxidase and ischemic preconditioning in isolated rat hearts: interference with postischemic functional recovery but no effect on infarct size reduction

Abstract: Monoamine oxidases (MAOs) have recently emerged as important mitochondrial sources of oxidative stress in the cardiovascular system. Generation of reactive oxygen species during the brief episodes of ischemic preconditioning (IPC) is responsible for the cardioprotection at reperfusion. The aim of this study was to assess the effects of two MAO inhibitors (clorgyline and pargyline) on the IPC-related protection in isolated rat hearts. Animals subjected to 30 min global ischemia and 120 min reperfusion were assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Supporting this claim, MAO inhibition in the settings of IPC has been reported to abolish cardioprotection (Di Lisa, unpublished observations, cited by [ 213 ]). However, in a recent study in isolated rat hearts subjected to a preconditioning protocol, we have demonstrated that bracketing the IPC episodes with MAO inhibitors did not interfere with the antinecrotic protection but potentiated the postischaemic functional recovery [ 214 ].…”
Section: Mitochondria As Sources Of Beneficial Rosmentioning
confidence: 99%
“…Supporting this claim, MAO inhibition in the settings of IPC has been reported to abolish cardioprotection (Di Lisa, unpublished observations, cited by [ 213 ]). However, in a recent study in isolated rat hearts subjected to a preconditioning protocol, we have demonstrated that bracketing the IPC episodes with MAO inhibitors did not interfere with the antinecrotic protection but potentiated the postischaemic functional recovery [ 214 ].…”
Section: Mitochondria As Sources Of Beneficial Rosmentioning
confidence: 99%
“…In both male and female rat hearts, ischemic preconditioning improves functional recovery following I/R, which is further enhanced in the presence of MAO inhibition by either clorgyline or pargyline. However, infarct size is similar among all preconditioned groups, regardless of the presence of MAO inhibitors, indicating that acute inhibition of MAOs potentiates the preconditioning-induced postischemic functional recovery without having any further effect on infarct size beyond that achieved by ischemic preconditioning [ 177 ].…”
Section: Monoamine Oxidases (Mao)mentioning
confidence: 99%